PENGARUH CITRA MEREK, KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN IPHONE DI KOTA BANDA ACEH - Eva Susanti (SUMBER INFORMASI MANAJEMEN BISNIS DAN AKUNTANSI, 2024)
The purpose of this study was to determine the influence of brand image, product quality, price, and promotion on iPhone purchasing decisions in Banda Aceh. The method used in this study was a quantitative approach. The results showed a significant influence between brand image, product quality, price, and promotion on iPhone purchasing decisions in Banda Aceh. The implications of this study indicate that brand image, product quality, price, and promotion influence iPhone purchasing decisions in Banda Aceh. This is because brand image can make it easier for consumers to recognize the product they want. Product quality can also influence consumer decisions because the higher the quality of a product, the higher the consumer's purchasing interest. Affordable prices can make it easier for consumers to gauge purchasing power, and promotions can provide the latest information to consumers.